Long-term effects of a flexible sigmoidoscopy screening after 17 years of follow up - Danış, Nilay; Tekin, Fatih (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Danış N, Tekin F. Long-term effects of a flexible sigmoidoscopy screening after 17 years of follow up. Turk J Gastroenterol 2017; 28: 427-8.